2011
DOI: 10.1212/wnl.0b013e318208811f
|View full text |Cite
|
Sign up to set email alerts
|

Muscle histology vs MRI in Duchenne muscular dystrophy

Abstract: Objective: There are currently no effective treatments to halt the muscle breakdown in Duchenne muscular dystrophy (DMD), although genetic-based clinical trials are being piloted. Most of these trials have as an endpoint the restoration of dystrophin in muscle fibers, hence requiring sufficiently well-preserved muscle of recruited patients. The choice of the muscles to be studied and the role of noninvasive methods to assess muscle preservation therefore require further evaluation. Methods:We studied the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 23 publications
8
128
0
Order By: Relevance
“…Despite pioneering NMRS work in forearm muscles of patients with DMD, 7 NMR data have since been primarily acquired in pelvic muscles or lower limbs in ambulant patients. [8][9][10][11][12][13][14][15][16][17][18][19][20] We recently reported the feasibility of using NMR for assessing the upper limb in nonambulatory patients. 21 Our main objective in the present study was to establish the baseline values for NMR and functional variables and at a 1-year follow-up time point period for ambulatory and nonambulatory patients with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite pioneering NMRS work in forearm muscles of patients with DMD, 7 NMR data have since been primarily acquired in pelvic muscles or lower limbs in ambulant patients. [8][9][10][11][12][13][14][15][16][17][18][19][20] We recently reported the feasibility of using NMR for assessing the upper limb in nonambulatory patients. 21 Our main objective in the present study was to establish the baseline values for NMR and functional variables and at a 1-year follow-up time point period for ambulatory and nonambulatory patients with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced non-invasive radio-imaging techniques have been found to be accurate in diagnosing and monitoring MD [25]. MRI has several advantages over other imaging techniques used in BMD.…”
Section: Discussionmentioning
confidence: 99%
“…In muscle diseases, MRI scans may be used to correlate the clinical phenotype with the muscle biopsy morphology and immunocytochemistry. Kinali et al [25] have demonstrated that MRI scanning can be a reliable tool to inform the choice of muscles to be assessed during clinical trials. In this paper, reporting data on a clinical trial based on antisense oligonucleotide in DMD, the results of the MRI scan serve as biomarkers of disease progression, in particular muscles, by identifying which ones are sufficiently preserved.…”
Section: Rare Diseases and Biomarkers: State-of-the-artmentioning
confidence: 99%